A study of pandemic and stigma effects in removal proceedings. Issue 3 (17th July 2022) - Peacock, Ian; Ryo, Emily
Abstract: This study examines how a rapid change in social perceptions of a national‐origin group triggered by the COVID‐19 pandemic influenced immigration judges' decision‐making in US removal proceedings. Using originally compiled court data on removal proceedings decided between 2019 and 2020, we applied a difference‐in‐differences framework to produce three key findings. First, consistent with theory of event stigma, Chinese respondents experienced a significantly higher removal rate during the early pandemic period. Second, consistent with theory of associative stigma, East and Southeast (E/SE) Asian respondents also experienced a significantly higher removal rate during the early pandemic period. Third, the removal rate declined for both Chinese and E/SE respondents during the later pandemic period, but this decline was more gradual and lagged for E/SE Asian than for Chinese respondents. Finally, increases in the number of cases involving Chinese respondents increased the removal rate for E/SE Asian respondents during the early months of the pandemic. The last two findings suggest that associative or indirect stigmatization may be harder to combat than direct stigmatization owing to the implicit nature of bias underlying associative stigma. This study highlights the socially constructed nature of national origin groups, and the importance of both direct and indirect stigmatization in the production of social inequality.